2015
DOI: 10.1177/0192623315618291
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Time Course of the Tissue Responses to Intramuscular Long-acting Paliperidone Palmitate Nano-/Microcrystals and Polystyrene Microspheres in the Rat

Abstract: Long-acting injectable (LAI) drug suspensions consist of drug nano-/microcrystals suspended in an aqueous vehicle and enable prolonged therapeutic drug exposure up to several months. The examination of injection site reactions (ISRs) to the intramuscular (IM) injection of LAI suspensions is relevant not only from a safety perspective but also for the understanding of the pharmacokinetics. The aim of this study was to perform a multilevel temporal characterization of the local and lymphatic histopathological/ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…A biphasic release profile differs from the more commonly observed initial peak followed by steady release; the mechanism behind the release profile observed in our study is unknown and may be related to unique absorption or release mechanisms. One such hypothesis was studied systematically by Darville et al with paliperidone palmitate nano/microsuspensions, where they demonstrated that key determinants of release in vivo were depot morphology, size, shape and local inflammatory response kinetics 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…A biphasic release profile differs from the more commonly observed initial peak followed by steady release; the mechanism behind the release profile observed in our study is unknown and may be related to unique absorption or release mechanisms. One such hypothesis was studied systematically by Darville et al with paliperidone palmitate nano/microsuspensions, where they demonstrated that key determinants of release in vivo were depot morphology, size, shape and local inflammatory response kinetics 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…61,85,86 Darville et al have observed the formation of granuloma, macrophage infiltration, and inflammation at the depot site post-IM injection of LA paliperidone palmitate, describing a multifactorial scenario at that site of injection. 87 Following administration of an injectable LA formulation, the removal of the nanoformulation and the discontinuation of treatment would require surgical expertise, if any complexities arise. To address this problem, recently, there is a high demand to modify existing injectable contraceptives to implants, namely, long-acting reversible contraceptives to ease the removal process in case of complications.…”
Section: Cell-based Delivery Systems a Variety Of Cell Types Have Bementioning
confidence: 99%
“…For example, for IM injectable LA formulations, only a relatively limited understanding of local tissue mechanisms influencing the drug release from the site of administration is currently available, and initial studies have indicated multifactorial scenarios in which chemical degradation, neoangiogenesis, and inflammation interact in the definition of drug absorption. 87 Moreover, PBPK models can support the simulation of drug distribution in animals defining opportunities to refine, replace, and reduce the use of preclinical species in the investigation of novel formulation. The coupling of animal and human PBPK models is an exciting prospect to inform the bridging of PK and therefore streamline the development of novel formulations.…”
Section: Physiologically Based Pharmacokineticsmentioning
confidence: 99%
“…Therefore, a detailed characterization of the histopathological response to i.m. injections of LAI nanosuspensions containing different stabilizers is essential, not only in the assessment of the tolerability and safety profile of the drug product (including the functional excipients) but also to obtain fundamental insights in the processes contributing to the pharmacokinetics of LAI formulations (Darville, van Heerden, Erkens, et al 2016). This was exemplified in a series of studies conducted by our group, which demonstrated that the granulomatous inflammatory reaction occurring upon i.m.…”
mentioning
confidence: 99%
“…The gradual yet extensive infiltration of CD68 þ macrophages within the formulation depot formed at the i.m. injection site was accompanied by increasing amounts of LAI formulation being phagocytosed over time (Darville, van Heerden, Erkens, et al 2016). This process of gradual uptake by macrophages and the intracellular relocation of large portions of the LAI dose meant that the intramacrophagic space became the primary site of drug dissolution and release.…”
mentioning
confidence: 99%